The Effectiveness of the GEPSI Electronic Library on the Knowledge of Communities in 3T (Disadvantaged, Frontier, and Outermost) Areas in Indragiri Hilir Regency - M.Raafi Fadhilah; Sukma Anggreini Tanjung; Arya Darma Wansyah; Anugrah Anugrah; Yoga Saputra (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
The development of information technology has encouraged the emergence of electronic library innovations as a solution to improve community literacy, particularly in 3T (Disadvantaged, Frontier, and Outermost) areas with limited access to information. This study aimed to analyze the effectiveness of the GEPSI Electronic Library in improving community knowledge in Tanjung Pidada Village, Tempuling District, Indragiri Hilir Regency. This research employed a quasi-experimental design using a one-group pre-test and post-test approach. The sample consisted of 30 respondents selected through total sampling technique. Data were collected using pretest and posttest questionnaires and analyzed statistically to determine differences before and after the intervention. The results showed that prior to the intervention, the majority of respondents had poor knowledge (73.3%), while after using the GEPSI e-library, most respondents were categorized as having good knowledge (73.3%). Statistical analysis indicated a p-value of 0.000 (p < 0.05), demonstrating a significant difference between pretest and posttest scores. It can be concluded that the GEPSI Electronic Library is effective in improving community knowledge in 3T areas. This program has the potential to become an innovative strategy for equalizing information access and enhancing community literacy.